Derivation of two iPSC lines from a sporadic ASD patient (NUIGi033-A) and a paternal control (NUIGi034-A) - Gallagher, Louise (My University, 2020)
Hundreds of rare risk factors have been identified for ASD, however, the underlying causes for ~70% of sporadic cases are unknown. Sporadic ASD models are thus essential for validating phenotypic commonality and drug suitability to the majority of patients. Here, we derived induced pluripotent stem cells (iPSCs) from one sporadic ASD child and one paternal control, using non-integrating Sendai viral methods. The iPSCs strongly expressed pluripotency markers and could be differentiated into three germ layers. Their normal karyotype was validated by genome SNP array. The availability of sporadic ASD-derived iPSCs offers an opportunity for phenotypic comparison with genetic ASD models.
Keywords: Sporadic ASD models; autism spectrum disorder (ASD); induced pluripotent stem cells (iPSCs)